Temperature dependence of magnetic and magnetotransport properties in BiFeO3 thin films by pulsed laser deposition. Issue 1636 (4th February 2014) - Tiberto, P.; Barrera, G.; Celegato, F.; Coïsson, M.; Rizzi, P.; Vinai, F.; Garcia Castro, A.C.; Salamanca-Riba, L.; Vispute, R.D.; Espinoza Beltran, F.J.; Sandaña, J. Muñoz
ABSTRACT: Multiferroic BFO/SRO/Si trilayers have been prepared by pulsed laser deposition in the form of thin films. As a function of the BFO layer thickness, magnetic and magneto-transport properties have been investigated at room temperature and down to 5 K. At low BFO layer thickness, a residual γ-Fe2 O3 phase, which interacts interfacially with the SRO and BFO layers, is responsible for moderately hard magnetic properties of the film. On increasing BFO layer thickness, more homogeneous deposits are obtained with uniform magnetic and magneto-resistive properties.